PENGARUH KEMAMPUAN PERENCANAAN WAKTU TERHADAP PENURUNAN STRES AKADEMIK MAHASISWA UNIVERSITAS AIRLANGGA - Alfi Putri Andini; Dita Mauliana; Feby Reza Anggraini (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The ability to use time efficiently plays an important role in improving an individual's overall productivity. Effective time planning can help students complete various tasks on time, avoid accumulation of work, and create a balance between academic activities and personal life. This study aims to analyze the ability of time planning to affect stress levels in college students. This study uses a quantitative method with a causal approach to explore the influence between the two variables. Data were obtained through a survey method involving university students as the study population. Meanwhile, the convenience sampling technique was used to obtain 100 respondents who became the research sample. The results of the analysis show that most students have a good level of time planning ability, although some still face obstacles in its application. Students' academic stress levels were found to vary which were influenced by various factors. The results of the analysis also show that there is a significant and valid relationship between time planning skills and stress levels of Universitas Airlangga students. Thus, effective time planning ability is proven to have a considerable contribution in reducing academic stress, contributing significantly to students' emotional well-being, and supporting optimal academic achievement.